(untitled) (Marketing Journal, 2026)
Abstract This article analyzes the role of the industrial sector in regional economic development from both theoretical and practical perspectives. The impact of industry on regional economic growth is examined through indicators such as production volume, employment level, investment activity, innovation performance, and export potential. The research is based on regional economic theory, cluster approach, and endogenous growth theory. The findings confirm that the industrial sector serves as a strategic driver of sustainable regional development. Keywords: regional economy, industrial sector, economic growth, cluster, investment, innovation, employment, gross regional product.